Implementation of The Problem Based Learning Model with Wordwall-Based Learning Media on Ecosystem Materials to Improve Student Activity and Learning Outcomes - Sinaga Dian Perayanti; Salome Rajagukguk; Asmina Herawaty Sinaga (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to determine the effectiveness of the application of the Problem Based Learning (PBL) model assisted by Wordwall-based learning media in improving student activity and learning outcomes in ecosystem material in class X of SMA Negeri 5 Pematangsiantar. The background of this study is based on the low activity and learning outcomes of students and the lack of innovation of the learning media used. The method used in this study is classroom action research (CAR). This study was conducted in two cycles consisting of four main stages: planning, action implementation, observation, and reflection. The subjects of this study were 36 students of class X-10 of SMA Negeri 5 Pematangsiantar. The results showed a significant increase in student learning outcomes from cycle I (60.94) to cycle II (84.56), with an increase of 23.6 points. Likewise, there was an increase in the percentage of learning completion, namely in cycle I of 27.78% (10 people) to 100% (36 people), in cycle II. From the observation results of student activity in cycle I obtained 60.15%, included in the less category and in cycle II 92.38%, included in the very good category thus there was an increase in student activity by 32.23%. The average N-Gain score of 0.83 shows that learning using the Problem Based Learning model with Wordwall-based learning media is very effective in increasing the activity and learning outcomes of class X-10 students of SMA Negeri 5 Pematangsiantar. The results of this study show an increase in student activity and learning outcomes in ecosystem material using the Problem Based Learning model with Wordwall-based learning media for class X-10 SMA Negeri 5 Pematangsiantar.